Roles of microRNAs in acute lung injury and acute respiratory distress syndrome: mechanisms and clinical potential - Wang, Pengyu; Lai, Dingyuan; Jin, Litong; Xue, Yi (Frontiers in Immunology, 2025)
Acute lung injury (ALI) is characterized by a systemic and excessive inflammatory response triggered by various direct or indirect pathogenic factors, resulting in increased permeability of the alveolar-capillary membrane and the accumulation of fluid in the alveolar and interstitial spaces. Clinical symptoms include reduced lung compliance, respiratory distress, and severe hypoxemia that is difficult to manage. Acute respiratory distress syndrome (ARDS) represents a more severe form of ALI. The incidence of ALI/ARDS among critically ill patients is approximately 10.4%, with a mortality rate as high as 45%. MicroRNA (miRNA) is a small, non-coding RNA molecule approximately 22 nucleotides in length, which plays diverse roles in cellular functions and exerts a significant regulatory influence on disease progression. Research related to miRNAs, particularly in the context of ALI/ARDS, has increased in recent years due to its crucial involvement in the disease process. This article elucidates the molecular mechanisms of miRNA and outlines the current research advancements in ALI/ARDS, offering novel insights into the pathogenesis and potential clinical applications of this condition.